Sensor for cysteine based on oxovanadium(IV) complex of Salen modified carbon paste electrode - Teixeira, MFS; Dockal, E. R.; Cavalheiro, ETG (Elsevier B.V., 2005)
The electrochemical behavior of a carbon paste electrode modified (CPEM) with N,N&PRIME;-ethylenebis(salicylideneiminato)oxovanadium(IV) complex ([(VO)-O-IV(Salen)]) was investigated as a new sensor for cysteine. Cyclic voltammetry at the modified electrode in 0.1 mol L-1 KCl Solution (pH 5.0) showed a single-electron reduction/oxidation of the Couple VO3+/VO2+. The CPEM with [VO(Salen)] presented good electrochemical stability in a wide pH range (4.0-10.0) and an ability to electrooxidate cysteine at 0.65 V versus SCE. These results demonstrate the viability of the use of this modified electrode as an amperometric sensor for cysteine determination. © 2004 Elsevier B.V. All rights reserved.
Keywords: N,N '-ethylenebis(salicylideneiminato)oxovanadium(IV); modified electrode; sensor; cysteine